Radiometric analysis of construction materials using Hpge Gamma-Ray spectrometry - Khandaker, Mayeen Uddin; Amin, Y.M.; Jojo, P.J.; Kassim, H.A. (Oxford University Press, 2012)
Concentrations of primordial radionuclides in common construction materials collected from the south-west coastal region of India were determined using a high-purity germanium gamma-ray spectrometer. Average specific activities (Bq kg(-1)) for U-238(Ra-226) in cement, brick, soil and stone samples were obtained as 54 +/- 13, 21 +/- 4, 50 +/- 12 and 46 +/- 8, respectively. Respective values of Th-232 were obtained as 65 +/- 10, 21 +/- 3, 58 +/- 10 and 57 +/- 12. Concentrations of K-40 radionuclide in cement, brick, soil and stone samples were found to be 440 +/- 91, 290 +/- 20, 380 +/- 61 and 432 +/- 64, respectively. To evaluate the radiological hazards, radium equivalent activity, various hazard indices, absorbed dose rate and annual effective dose have been calculated, and compared with the literature values. Obtained data could be used as reference information to assess any radiological contamination due to construction materials in future.